Preparation method of photo-responsive Fe < 3 + >-doped carbon dot wood-based phase change energy storage material

By doping Fe3+ doped carbon dots in polyethylene glycol and combining with delignin wood, a photoresponsive Fe3+ doped carbon dot wood-based phase change energy storage material is solved, and polyethylene glycol is prone to leakage at high temperatures and the problem of low light-thermal conversion capability, the efficient energy storage and stability of materials are achieved, and are suitable for areas such as building energy conservation.

CN119242271APending Publication Date: 2025-01-03LONGTAN HYDROPOWER DEV CO LTD HESHAN POWER GENERATION CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411368473.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

As a commonly used organic phase change material, polyethylene glycol is prone to melt leakage at high temperatures, and its photothermal conversion ability is low, and it fails to fully utilize the latent heat value of phase change. Existing packaging methods such as microcapsule method and polymer matrix recombination The method has problems of complex preparation process and high cost.

Method used

The preparation method of photoresponsive Fe3+ doped carbon dot wood-based phase change energy storage material is adopted. By mixing Fe3+ doped carbon dot powder with polyethylene glycol in delignin wood, it is vacuum impregnation and drying to form Fe3+ Doped carbon dot wood-based composite phase change energy storage material, chemically encapsulated using the hydroxyl functional groups of wood, enhances the morphological stability and thermal enthalpy properties of the material.

Benefits of technology

The leakage prevention rate at 60°C is less than 1%, maintaining the thermal enthalpy performance of polyethylene glycol of 90.10%, and can quickly heat up and continuously maintain heat under solar excitation. It is suitable for building energy conservation and agricultural production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242271A_ABST
    Figure CN119242271A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a photo-responsive Fe < 3 + >-doped carbon dot wood-based phase change energy storage material, which comprises the following steps: step 1, dissolving Fe < 3 + >-doped carbon dot powder in ethanol to obtain a carbon dot solution; 2, melting polyethylene glycol in a water bath, pouring the molten polyethylene glycol into the carbon dot solution, and stirring and mixing to obtain a Fe-CDs (at) PEG composite phase change material; 3, the Fe-CDs and PEG composite phase change material is placed in a constant-temperature vacuum box to be in a molten state, lignin-removed wood is added, vacuumizing is conducted, normal pressure is recovered, a sample is taken out, the phase change material on the surface is wiped away through filter paper, and the Fe < 3 + >-doped carbon dot wood-based composite phase change energy storage material is obtained. Wood is used as a supporting framework, physical packaging can be achieved, and meanwhile polyethylene glycol is chemically packaged through a large number of hydroxyl functional groups contained in the wood to prevent the polyethylene glycol from leaking; the polyethylene glycol as an energy storage core material is combined with the Fe < 3 + >-doped carbon dots capable of generating red light under the excitation of sunlight, so that the energy storage capacity of the polyethylene glycol can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of phase change energy storage materials. More specifically, the present invention relates to a light-responsive Fe 3+ Preparation method of carbon doped wood-based phase change energy storage material. Background Art

[0002] Polyethylene glycol (PEG2000) is a popular organic phase change energy storage material. PEG stores / releases a large amount of heat energy during the phase change process. It has attracted much attention due to its remarkable characteristics such as high phase change latent heat, excellent chemical stability, safety and non-toxicity, and low cost. The chemical structure of polyethylene glycol is HO(CH2CH2O)nH. The melting point of PEG2000 is about 64-66℃, and it is a waxy solid at room temperature. PEG has been widely used in energy-saving fields such as building energy conservation. However, PEG is prone to melting and leakage at high temperatures, and its photothermal conversion capacity is low, which makes it unable to fully utilize the phase change latent heat value of PEG. In the current research progress, people often use the following methods to prevent the leakage of organic phase change energy storage materials, such as porous matrix adsorption method, microencapsulation method, polymer matrix recombinant method, etc. The microencapsulation method and polymer matrix recombinant method have the disadvantages of complex preparation process and high cost. The porous matrix adsorption method is one of the relatively low-cost encapsulation composite methods. However, in the prior art, inorganic porous matrices are usually used for adsorption, which have the disadvantages of being difficult to mine and non-degradable. Therefore, it is necessary to find a supporting material that is both economical and environmentally friendly and easy to prepare, so as to give full play to the phase change latent heat value of PEG. Summary of the invention

[0003] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.

[0004] One object of the present invention is to provide a light-responsive Fe 3+ The invention discloses a method for preparing a carbon dot-doped wood-based phase change energy storage material, which can solve the problems of low thermal conductivity, easy leakage and low economic added value of wood during phase change of polyethylene glycol as a commonly used organic phase change material.

[0005] In order to achieve these objects and other advantages of the present invention, a photoresponsive Fe 3+ A method for preparing a carbon dot-doped wood-based phase change energy storage material comprises the following steps:

[0006] Step 1: Fe 3+ The doped carbon dot powder was dissolved in ethanol to obtain Fe 3+ doping carbon dot solution;

[0007] Step 2: Melt polyethylene glycol in a water bath and pour in Fe 3+The doped carbon dots solution was stirred and mixed to obtain Fe-CDs@PEG composite phase change material;

[0008] Step 3: The Fe-CDs@PEG composite phase change material is placed in a constant temperature vacuum box to make it in a molten state, and then the delignified wood is added and vacuumed to restore the normal pressure. The sample is taken out and the surface phase change material is wiped off with filter paper to obtain Fe 3+ Carbon dot-doped wood-based composite phase change energy storage materials.

[0009] Preferably, Fe 3+ The preparation method of the doped carbon dot powder is as follows: dopamine hydrochloride, o-phenylenediamine, ferric chloride hexahydrate and anhydrous ethanol are taken, stirred and dissolved, and then placed in a tetrafluoroethylene-lined reactor; the reactor is then transferred to a muffle furnace for heating and reaction; after the heating is completed, the solution in the reactor is centrifuged, and the supernatant is placed in a dialysis bag for dialysis; after the dialysis is completed, the dialysate is subjected to vacuum freeze-drying treatment to obtain Fe 3+ Doped carbon dot solid powder.

[0010] Preferably, the mass ratio of dopamine hydrochloride, o-phenylenediamine and ferric chloride hexahydrate is 1-5:1-5:1.

[0011] Preferably, the temperature of the furnace is 180-220°C and the reaction time is 10-12h.

[0012] Preferably, the centrifugal speed is 8000 r / min and the centrifugal time is 15 min. The unreacted products are removed by centrifugation to make them precipitate.

[0013] Preferably, the molecular weight of the dialysis bag is 1000Da, and the dialysis time is 40-50h. Small molecule impurities are removed by dialysis.

[0014] Preferably, the drying treatment time is 14-48 hours.

[0015] Preferably, polyethylene glycol and Fe 3+ The mass ratio of the doped carbon dot powder is 3000-4000:1.

[0016] Preferably, the preparation method of delignified wood is to prepare a sodium chlorite solution with a mass fraction of 0.1-2%, adjust the pH value to 4-5, add wood chips to the solution, treat it in a water bath to remove lignin, and after the water bath, perform vacuum freeze drying to obtain delignified wood.

[0017] Preferably, in step three, the operation of evacuating the air and restoring the pressure to normal is repeated 1-5 times.

[0018] The present invention has at least the following beneficial effects:

[0019] First, the present invention impregnates Fe in delignified wood3+ The mixture of doped carbon dots and polyethylene glycol makes its morphology extremely stable, with a leakage rate of less than 1% in a 60°C anti-leakage test and a complete morphology and structure.

[0020] Second, the present invention will Fe 3+ The phase change energy storage composite material prepared by doping carbon dots and impregnating polyethylene glycol in delignified wood has an enthalpy of 137.04 J / g, and the enthalpy of polyethylene glycol itself is 149.5 J / g, maintaining 90.10% of the thermal enthalpy performance of polyethylene glycol.

[0021] Third, the present invention uses wood as a supporting skeleton, which can not only achieve physical encapsulation, but also use the large number of hydroxyl functional groups in wood to chemically encapsulate polyethylene glycol to prevent its leakage; polyethylene glycol is used as an energy storage core material and Fe2O3, which produces red light under the excitation of sunlight. 3+ The doped carbon dots can enhance the energy storage capacity of polyethylene glycol. After the illumination ends, the heat stored in the energy storage composite material can be used for continuous heat preservation. Under simulated sunlight, the temperature rises from room temperature to 65.4°C in a short time, and after the xenon lamp is turned off, the temperature remains at 40°C after 1 hour. Therefore, the material of the present invention can be applied to the fields of building energy conservation, agricultural production, etc.

[0022] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The structural analysis results of CDs, including (a) transmission electron microscope image of CDs, (b) lattice spacing image of CDs, (c) size distribution image of CDs, and (d) XRD image of CDs.

[0024] Figure 2 The results of the structural analysis of Fe-CDs; (a) TEM image of Fe-CDs; (b) lattice spacing of Fe-CDs; (c) size distribution of Fe-CDs; (d) XRD image of Fe-CDs;

[0025] Figure 3 The results of CDs composition analysis; (a) Raman image of CDs; (b) FTIR image of CDs; (c) UV-visible absorption image of CDs;

[0026] Figure 4 The composition analysis results of Fe-CDs; (a) Raman image of Fe-CDs; (b) FTIR image of Fe-CDs; (c) UV-Vis absorption image of Fe-CDs;

[0027] Figure 5The results of elemental analysis of CDs; (a) the content of each element of CDs; (b) the XPS graph of the C element of CDs; (c) the XPS graph of the N element of CDs; (d) the XPS graph of the O element of CDs;

[0028] Figure 6 The results of elemental analysis of the composition of Fe-CDs; (a) element content diagram of Fe-CDs; (b) C element XPS image of Fe-CDs; (c) N element XPS image of Fe-CDs; (d) O element XPS image of Fe-CDs; (e) element XPS image of Fe-CDs;

[0029] Figure 7 The results of CDs fluorescence property analysis are shown in Figure 1. (a) CDs excitation spectrum at 650 nm; (b) CDs emission spectrum at 570 nm.

[0030] Figure 8 The results of the fluorescence property analysis of Fe-CDs; (a) the mechanism diagram of the red shift of Fe-CDs emission wavelength and the enhancement of Fe-CDs non-radiative relaxation process; (b) the excitation spectrum of Fe-CDs at 660nm; (c) the emission spectrum of Fe-CDs at 562nm;

[0031] Fig. 9 FTIR graph of delignified wood;

[0032] Fig.10 The microstructure analysis results of CDs-shaped wood-based phase change energy storage materials; (a, d) are cross-section and longitudinal sections of natural wood; (b, e) are cross-section and longitudinal sections of delignified wood; (c, f) are cross-section and longitudinal sections of delignified wood impregnated with polyethylene glycol and carbon dots;

[0033] Fig.11 The microstructure analysis results of Fe-CDs shaped wood-based phase change energy storage materials; (a) SEM image of the cross section of delignified wood impregnated with Fe-CDs and PEG; (b) SEM image of the longitudinal section of delignified wood impregnated with Fe-CDs and PEG;

[0034] Fig.12 The thermal performance analysis results of CDs-shaped wood-based phase change energy storage materials; (a) DSC graph of phase change energy storage materials; (b) TG image of phase change energy storage materials; (c) DTG curve graph; (d) cycle test graph of phase change energy storage materials;

[0035] Fig.13The results of the photothermal conversion analysis of Fe-CDs shaped wood-based phase change energy storage materials; (a) is the DSC image of the phase change energy storage material; (b) is the TG image of the phase change energy storage material; (c) is the DTG curve; (d) is the cycle test image of the phase change energy storage material;

[0036] Fig.14 Thermal imaging of phase change energy storage materials loaded with different concentrations of CDs;

[0037] Fig.15 Analysis of the photothermal conversion of CDs shaped wood-based phase change energy storage materials; (a) PEG / DW and PEG@CDs / DW phase change energy storage materials and energy storage and release time; (b) CDs shaped wood-based phase change energy storage physical image; (c) CDs shaped wood-based phase change energy storage thermal imaging normal temperature image; (d) CDs shaped wood-based phase change energy storage thermal imaging heating image;

[0038] Fig.16 This is the thermal imaging temperature rise diagram of the phase change energy storage material loaded with different concentrations of Fe-CDs;

[0039] Fig.17 The results of the Fe-CDs shaped wood-based phase change energy storage material shaped analysis; (a) PEG / DW and PEG@Fe-CDs / DW phase change energy storage materials and energy storage and release time; (b) Fe-CDs shaped wood-based phase change energy storage physical image; (c) Fe-CDs shaped wood-based phase change energy storage thermal imaging normal temperature image; (d) CDs-loaded shaped wood-based phase change energy storage thermal imaging temperature rise image;

[0040] Fig.18 The results of the anti-leakage ability analysis of CDs-shaped wood-based phase change energy storage materials; (a) the bonding mechanism diagram of phase change energy storage materials; (b) pure polyethylene glycol, wood-based phase change energy storage materials and Fe-CDs-shaped wood-based phase change energy storage materials;

[0041] Fig.19 The leakage prevention test analysis results of Fe-CDs shaped wood-based phase change energy storage materials. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0043] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0044] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0045] <Test content>

[0046] 1. Preparation of materials

[0047] 1.1 Preparation of delignified wood

[0048] Prepared with 1wt% NaClO2 solution, and adjusted its pH to 4.6 with glacial acetic acid. Balsa wood chips (size 30x30x3 mm) were placed in an environment of 80°C for 18h until their color turned white. Subsequently, the delignified wood sample was washed three times with deionized water and ultrasonically cleaned in deionized water for 20min to remove most of the chemical residues. After ultrasonic cleaning, the delignified wood was placed in a refrigerator for freezing for 12h, followed by vacuum freeze drying for 24h to finally obtain delignified wood (DW).

[0049] 1.2 Preparation of carbon dots (CDs)

[0050] Weigh 0.1g of dopamine hydrochloride and 0.1g of o-phenylenediamine, then add 15ml of anhydrous ethanol and stir thoroughly to dissolve the drugs. Then, pour the completely dissolved solution into a polytetrafluoroethylene-lined reactor, and place the reactor in a muffle furnace and react at 180°C for 12 hours. After the reactor is naturally cooled, centrifuge the reactor solution (speed is 8000r / min, lasting 15min), then wash with anhydrous ethanol and centrifuge again twice, and finally take out the supernatant. Put the supernatant into a dialysis bag and continue dialysis for 48 hours. After the dialysis is completed, put the CDs solution into the refrigerator for freezing. After freezing, place it in a vacuum freeze dryer for freeze drying for 48 hours to finally obtain carbon dots (CDs) powder.

[0051] 1.3 Preparation of CDs-shaped wood-based phase change energy storage materials

[0052] A certain mass concentration of CDs was dissolved in 5 mL of anhydrous ethanol. Subsequently, this solution was evenly distributed into 30 g of molten PEG. The formula is shown in Table 1. Under 70°C water bath conditions, magnetic stirring was continued for 20 min to ensure that the components were fully mixed. Next, the mixed solution was transferred to a 50 mL beaker, and a piece of DW wood chip (balsa wood chip with a size of 30×30×3 mm) was placed in each beaker. The beaker was placed in a vacuum oven at 70°C, the vacuum pump was used to evacuate the air, and vacuum impregnation was performed for 30 minutes. To ensure the adequacy of the impregnation effect, the vacuum-assisted impregnation process was repeated three times in this experiment. The phase change material was successfully prepared. For the purpose of distinction, this experiment marks the phase change energy storage materials undoped with CDs as PEG / DW, and the phase change energy storage materials doped with CDs as PEG / DW, PEG@CDs-1.2 / DW, PEG@CDs-1.5 / DW, PEG@CDs-1.8 / DW, and PEG@CDs-2.1 / DW.

[0053] Table 1 Recipe

[0054]

[0055] 1.3 Preparation of Iron Carbon Dots (Fe-CDs)

[0056] Weigh 0.1 g dopamine hydrochloride, 0.1 g o-phenylenediamine, and 0.05 g ferric chloride hexahydrate, add 15 ml anhydrous ethanol and stir to dissolve. Prepare iron-doped carbon dots (Fe-CDs) according to the method provided in 1.2 Preparation of carbon dots (CDs).

[0057] 1.4 Preparation of Fe-CDs-shaped wood-based phase change energy storage materials

[0058] According to Table 2, Fe-CDs of a certain mass concentration was dissolved in 5 ml of anhydrous ethanol. Then, Fe-CDs was prepared according to the method provided in 1.3 Preparation of CDs shaped wood-based phase change energy storage material. 3+ Carbon dot-doped wood-based composite phase change energy storage materials are labeled as PEG / DW, PEG@Fe-CDs-1.2 / DW, PEG@Fe-CDs-1.5 / DW, PEG@Fe-CDs-1.8 / DW, and PEG@Fe-CDs-2.1 / DW.

[0059] Table 2 Recipe

[0060]

[0061] 2 Performance Testing and Characterization

[0062] 2.1 High-resolution transmission electron microscopy analysis

[0063] A high-resolution transmission electron microscope (TEM) was used to observe the carbon dot morphology at an accelerating voltage of 200KV to characterize the structure and morphology. The carbon dot sample preparation process is as follows: a small amount of carbon dot solution is diluted with anhydrous ethanol, then ultrasonicated for 30 minutes, and then the evenly dispersed solution is dripped onto the copper grid and dried at room temperature.

[0064] 2.2 Chemical structure analysis

[0065] Fourier transform infrared spectroscopy (FTIR) analysis of carbon dots and wood chemical structure. The operation steps are as follows: grind the sample into powder, then mix it with potassium bromide at a ratio of 1:100, grind it evenly with a mortar, take an appropriate amount of the mixed powder and put it into a mold, use a tablet press to make a thin slice, and then test it. The scanning range is 4000cm –1 —500cm –1 .

[0066] 2.3 Crystallization properties

[0067] The crystallinity of carbon dots was characterized by X-ray diffractometer (XRD). The device used CuKα as the X-ray source, the scanning speed was 5° / min, and the 2θ range was 10°-90°.

[0068] 2.4 X-ray photoelectron spectrometer analysis

[0069] X-ray photoelectron spectroscopy (XPS) was used to perform chemical analysis on the surface of CDs, and wide scans of C, O, and N were performed.

[0070] 2.5 Absorbance analysis

[0071] The carbon dot solution was scanned using a UV-visible spectrophotometer to obtain the functional group absorption spectrum of the carbon dots. The measurement speed was 1 nm / s and the wavelength range was 200-800 nm.

[0072] 2.6 Fluorescence performance analysis

[0073] The fluorescence spectrum of the carbon dot solution was recorded by a fluorescence spectrophotometer to obtain the optimal excitation and emission wavelengths of CDs.

[0074] 2.7 Micromorphology Characterization

[0075] The cross-section and longitudinal section microstructures of the phase change energy storage material were observed by field emission scanning electron microscopy (SEM). During the experiment, the pre-cut samples were glued to the conductive glue with tweezers, and the samples were tested after gold spraying. During the test, the magnification was adjusted until the sample was clearly visible and the sample was observed.

[0076] 2.8 Thermal performance characterization

[0077] The thermal performance of the energy storage material was tested using a differential scanning calorimeter under 50 ml / min nitrogen conditions. Weigh 3-5 mg of the sample, first heat it from 25°C to 70°C at a rate of 2°C / min, balance for 5 minutes, and then cool it from 70°C to 25°C at a rate of 2°C / min.

[0078] 2.9 Thermal stability analysis

[0079] The thermal stability of phase change energy storage materials and carbon dots was tested using a thermogravimetric analyzer. 5-10 mg of sample was taken each time and tested at a nitrogen flow rate of 50 ml / min and a heating rate of 10 °C / min, with a heating range of 30-600 °C.

[0080] 2.10 Surface temperature change and thermal storage performance test

[0081] A xenon lamp (model CEL-HXF300, from Zhongjiao Jinyuan) was used, and the light energy density was set to 200 mw / cm 2 To irradiate the phase change energy storage material. The solar light absorption experiment was simulated, and the surface temperature change of the phase change energy storage material during the xenon lamp radiation was recorded and photographed using an infrared thermal imager. When the surface temperature of the sample reached stability, the sample was removed and allowed to cool naturally to room temperature. At the same time, the surface temperature change of the sample during the cooling process was recorded and photographed using an infrared thermal imager.

[0082] 2.11 Cyclic stability analysis

[0083] The phase change energy storage material sample was placed in a petri dish and then heated in an oven at 60°C for 30 minutes. After the sample was heated, it was taken out and placed on the experimental workbench and cooled to room temperature. Then, the energy storage material was placed in the oven and heated again, and this cycle was repeated 50 times. Finally, the sample was tested using a differential scanning calorimeter (DSC) to analyze its thermal cycling stability.

[0084] 2.12 Calculation method of impregnation rate of phase change energy storage materials

[0085]

[0086] V K =V wood ×V porosity (2.2)

[0087]

[0088] V k represents the pore volume of wood; V impre represents the impregnation rate; V wood is the volume of wood; V porosity is the porosity of wood.

[0089] 2.13 Calculation method of latent heat efficiency of phase change energy storage materials

[0090]

[0091] 2.14 Calculation method of photothermal conversion efficiency

[0092]

[0093] Tmax: maximum temperature of phase change energy storage material; T sur is the lowest temperature of phase change energy storage material; Q dis is heat loss; I is electrical power; A λ is the absorbance; m is the mass of the phase change energy storage material; C is the specific heat capacity of the phase change material; τ is the integration time.

[0094] 3 Results Analysis

[0095] 3.1 Structural analysis of carbon dots (CDs) and iron-doped carbon dots (Fe-CDs)

[0096] The morphology and particle size of CDs and Fe-CDs were analyzed by TEM. The average particle size of carbon dots (CDs) is 2.86nm, and the lattice spacing is 0.33nm, which corresponds to the graphene (110) lattice plane, indicating that the prepared carbon dots have a graphene layered structure, which is conducive to thermal conductivity ( Figure 1 ac). X-ray diffraction results show that the peak of the XRD curve of carbon dots at 25° is attributed to the (002) crystal plane of the graphite structure ( Figure 1 d), further proving that CDs have a graphene structure. The average particle size of Fe-CDs is 7.56nm ( Figure 2 c), its particle size is larger than that of carbon dots without iron ions because Fe 3+ Stable coordination bonds are formed with CDs. Compared with non-metal ions, metal ions have more electrons and unoccupied orbits and larger atomic radius. After doping with metal ions, the electron density distribution and energy gap of CDs change dramatically, so that the physical and chemical properties of CDs can be adjusted, which is ultimately manifested as the size of carbon dots increases after iron ions are doped. Figure 2 (b) shows that the Fe-CDs lattice spacing is 0.31nm, corresponding to the (100) lattice plane of graphene. The graphene (100) crystal plane spacing is an important factor in the performance of graphene. It causes the graphene (100) electron cloud to overlap strongly and the lattice plane spacing to be small, indicating that the interaction between the graphene layered structures is enhanced. The X-ray diffraction pattern (XRD) of Fe-CDs shows a peak of the 100 crystal plane of the graphite structure at 24° ( Figure 2 d) Due to carbon dots and doped Fe 3+The graphene crystal planes of carbon dots are different, and the graphene lattice spacing of Fe-CDs is smaller, which enhances the heat transfer capacity between the graphene layer structures in Fe-CDs. 3+ The thermal conductivity of CDs is further enhanced.

[0097] 3.2 Composition analysis of carbon dots (CDs) and iron-doped carbon dots (Fe-CDs)

[0098] Figure 3 The chemical composition analysis diagram of CDs. Figure 3 (a) shows the Raman spectrum of CDs, with the G band peak at 1590 cm -1 The sp 2 Stretching vibration is a characteristic peak of graphite. The D band peak is located at 1345cm -1 The sp 3 Breathing vibrations are related to lattice defects and disorder in the material. The degree of graphitization can be measured by sp 2 / sp 3 In CDs, the ratio of G band to D band (IG / ID) is 6.9%, which is a graphite structure that is good for thermal conductivity. Figure 3 (b) FTIR spectrum analysis, 3225 and 3060 cm -1 The peaks at 1130 and 756 cm are NH and -OH stretching vibration peaks. -1 The peaks at 1597 cm-1 are C-OH and =CH stretching vibration peaks. -1 It is the C=O stretching vibration peak, indicating that the carbon dots are rich in amino, hydroxyl and carboxyl functional groups. Figure 3 (c) The UV-Vis absorption spectrum of the carbon dots shows broad absorption bands at 234-360 nm and 420-600 nm, indicating that CDs absorb in both the UV and visible regions. 2 The π-π* transition of the C=C bond in the system is related to the n→π* transition.

[0099] Figure 4 This is the chemical composition analysis diagram of Fe-CDs. Figure 4 (a) shows the Raman spectrum of Fe-CDs, with the G band peak at 1585 cm -1 The sp 2 Stretching vibration is a characteristic peak of graphite. The D band peak is located at 1348cm -1 The sp 3 Breathing vibration. The degree of graphitization can be measured by sp 2 / sp 3The ratio of G band to D band (IG / ID) in Fe-CDs is 16.6%, while the ratio of G band to D band in CDs is 6.9%. The larger the ratio of G band to D band, the better the degree of graphitization. This further shows that the degree of graphitization of Fe-CDs is better than that of CDs, and its thermal conductivity will also be better. Figure 4 (b) at 3328 and 2926 cm -1 The peaks at 1034 cm-1 are NH and -OH stretching vibration peaks. -1 The peak at 1743 cm -1 The peak of C=O stretching vibration is 590 cm -1 The Fe-O absorption peak proves that Fe 3+ Successfully doped with carbon dots to form coordination bonds ( Figure 6 b) In addition, Figure 4 b shows the C=O peak intensity of Fe-CDs compared with CDs ( Figure 3 The peak intensity of the C=O functional group in a) is enhanced, which indicates that Fe 3+ Doping increases the proportion of C=O functional groups. The ultraviolet-visible light absorption (UV-Vis) of Fe-CDs has broad absorption bands at 230-310nm and 400-600nm, indicating that Fe-CDs have obvious absorption in both the ultraviolet and visible regions. The reason is related to the π-π* transition of the C=C bond in the aromatic system containing the C=N bond ( Figure 4 c), it has a synergistic effect with increasing the ratio of C=O functional groups, thereby promoting the red shift of the Fe-CDs fluorescence emission wavelength and improving the photothermal conversion capacity of the phase change energy storage material.

[0100] 3.3 Analysis of composition elements of Cdots and Fe-doped Cdots

[0101] To further analyze the surface chemical composition of CDs, XPS analysis was performed on the carbon dots. The components of CDs mainly include C (75.79%), O (11.54%) and N (12.67%) ( Figure 5 a). The N1s spectrum can be fitted into three peaks (398.1, 399.5 and 400.9 eV), corresponding to pyrrolic N, pyridinic N and graphitic N, respectively. Figure 5 c) The 531.5 and 532.6 eV peaks in the O1s spectrum are attributed to the C=O and C-OH groups ( Figure 5 d), which is consistent with the infrared spectrum results. The C1s spectrum shows that SP 2 -C (283.7ev). Carbon atoms are represented by SP 2 Hybridization forms a two-dimensional graphene layer, which corresponds to the Raman test results in the above study, indicating that CDs are rich in SP2 Stretching vibration carbon, C in CDs forms a stable structure ( Figure 5 b).

[0102] XPS analysis of Fe-CDs showed that Fe-CDs mainly contained C (75.51%), O (7.34%), N (16.94%) and Fe 3+ (0.19%) Figure 6 a). The N1s spectrum can be fitted into three peaks (398.2, 399.0 and 400.6 eV), corresponding to pyridinic N, pyrrolic N and graphitic N ( Figure 6 c). The 531.7 and 533.1 eV peaks in the O1s spectrum are attributed to the C=O and C-OH groups, respectively ( Figure 6 d) The XPS spectrum of Fe2p3 shows different peaks, indicating that Fe 3+ The valence state still exists stably ( Figure 6 e) Compared with the XPS images of CDs, the content of graphitic N in the N1s spectrum of Fe-CDs increases, which is consistent with the Figure 4 The Raman test results of a are consistent. The ratio of the G band to the D band of Fe-CDs is higher than that of CDs, that is, the degree of graphitization of Fe-CDs is stronger than that of CDs ( Figure 6 b) The reason is that Fe 3+ Interaction with CDs forms coordination bonds, which helps to increase the degree of graphitization. Increasing the degree of graphitization of carbon dots helps to produce more red-shifted fluorescence and enhances the photothermal conversion capacity of Fe-CDs.

[0103] 3.4 Analysis of fluorescence properties of carbon dots (CDs) and iron-doped carbon dots (Fe-CDs)

[0104] The photothermal conversion characteristics of carbon dots were studied by analyzing their fluorescence properties. Figure 7 The best excitation and emission wavelengths for CDs are shown in Figure 2. Ethanol solutions of CDs appear red under visible light excitation, such as Figure 7 (b) As shown in the upper right corner of the picture. The optimal excitation wavelength of CDs in the visible light region is 570nm, and the corresponding optimal emission wavelength is 650nm ( Figure 7 a, b), because its wavelength is between 600-700nm, which belongs to the red light region. When CDs are excited by visible light wavelengths to emit red light, when the incident light is higher than the band gap transition energy, due to the action of photons, its electrons transition from the ground state (S0) to the excited singlet state (S1). When the electrons relax from the lowest vibration energy level S1 and return to the ground state, they will radiate heat. Therefore, CDs can be used as photothermal conversion agents, and they have good photothermal conversion application prospects.

[0105] Figure 8The Fe-CDs fluorescence test results show that the ethanol solution of Fe-CDs appears red under visible light excitation, and Fe-CDs emits best at a wavelength of 660nm, and its optimal excitation wavelength in the visible light region is 562nm ( Figure 8 b). Compared with the emission wavelength of CDs, 650nm ( Figure 7 ), Fe-CDs emit light at a wavelength of 660 nm under visible light excitation, and then red-shift to a range of 600-660 nm ( Figure 8 c), which indicates that Fe-CDs have a better red emission range. This can be attributed to the fact that Fe 3+ After doping, the percentage of C=O and the degree of graphitization in CDs are increased relative to CDs. Previous studies have shown that the increase in the C=O ratio and the degree of graphitization can promote the red light emission of carbon dots. Therefore, when the emission wavelength of Fe-CDs is red-shifted compared to the emission wavelength of CDs, when the incident light is higher than the band gap transition energy, due to the action of photons, its electrons transition from the ground state (S0) to the excited singlet state (S1). When the electrons relax from the lowest vibrational energy level S1 and return to the ground state, the heat radiated will be higher than the heat radiated by CDs, thereby improving the non-radiative relaxation process (thermal radiation) capability of Fe-CDs and enhancing the photothermal conversion capability ( Figure 8 a).

[0106] 3.5 Analysis of chemical composition of delignified wood

[0107] The porosity of natural balsa wood was further increased by treating it with 1 wt% NaClO2 and studying the effect of different time on the lignin content to further increase the porosity of the wood ( Fig. 9 ). Due to the presence of lignin, natural wood usually appears yellow. After delignification, the color of the wood changes to white. -1 The characteristic peaks of aromatic skeletons are shown at the top, which are the characteristic peaks of lignin structure. When natural wood is treated with 1wt% NaClO2 for 6h and 12h respectively, a small amount of characteristic peaks of lignin can still be observed in the wood. However, when the treatment time is extended to 18h, the characteristic peaks of lignin completely disappear, indicating that the lignin in the wood has been completely removed. Balsa wood, as a wood with high porosity (82.58%), has a porosity of 91.97% after being treated with 1wt% NaClO2 solution. Therefore, after delignification treatment, the wood can be filled with more phase change energy storage materials, thereby increasing its thermal energy density.

[0108] 3.6 Microstructure analysis of carbon dots (CDs) and iron-doped carbon dots (Fe-CDs) shaped wood-based phase change energy storage materials

[0109] In order to compare the changes in the micromorphology and pore structure of natural wood (NW), delignified wood (DW) and CDs loaded phase change energy storage materials, SEM analysis was carried out on the samples. Fig.10 As shown, the cross-sectional interstitial spaces of natural wood are often blocked by the presence of lignin ( Fig.10 a). The interior of its longitudinal ducts will also be affected by lignin compounds and become blocked ( Fig.10 d). After delignification treatment, the cross-cutting pores and longitudinal duct pores of the wood are clear, and the pore blockage is reduced compared with that of natural wood ( Fig.10 b, e), the porosity of natural wood increased from 82.58% to 91.97%, which is conducive to encapsulating more polyethylene glycol (PEG). When the delignified wood is impregnated with PEG, the impregnation effect is significant. Whether it is the cross section or the longitudinal section, PEG can completely fill the wood ( Fig.10 c, f). This is because the cellulose in delignified wood contains abundant hydroxyl functional groups, which can form hydrogen bonds with the hydroxyl groups of PEG to prevent leakage of PEG. Since CDs contain a large number of hydroxyl and carboxyl functional groups, they are mixed with PEG and impregnated in the DW pores as "cross-linking points", which restrict the movement of PEG molecular chains to improve the anti-leakage ability of phase change energy storage materials. In addition, the ductal mesoporous structure contained in the wood also helps to fix the molecular chains of PEG in the wood through physical forces, such as capillary force and surface tension, so that the anti-leakage ability of phase change energy storage materials is further improved.

[0110] Fig.11 The SEM analysis results show that in the Fe-CDs-loaded shaped phase change energy storage material, PEG is fully impregnated in the wood pore structure. Whether it is a cross section or a longitudinal section, PEG and iron-doped carbon dots can completely fill the wood without interface separation. This can be attributed to the rich hydroxyl functional groups on the pore surface of delignified wood, the hydrogen bonding with the hydroxyl groups in PEG, and the "cross-linking effect" between the rich amino and carboxyl groups on the surface of Fe-CDs and the hydroxyl groups of the PEG molecular chain, which restricts the movement of the PEG molecular chain, which is manifested in the macroscopic improvement of the anti-leakage ability of the phase change energy storage material. In addition, the ductal mesoporous structure contained in the wood also helps to fix the PEG molecular chain in the wood through physical forces such as capillary force and surface tension.

[0111] 3.7 Analysis of the impregnation rate of carbon dots (CDs) and iron-doped carbon dots (Fe-CDs) in shaped wood-based phase change energy storage materials

[0112] The impregnation ratio of PEG in wood reflects the latent heat efficiency of phase change energy storage materials. The higher the impregnation ratio, the better the latent heat efficiency of phase change energy storage materials. Table 3 shows the encapsulation rates of different phase change materials impregnated in natural wood (NW) and delignified wood (DW). The impregnation rates of PEG / NW and PEG@CDs-1.8 / NW do not exceed 30%, while the impregnation rates of PEG / DW and PEG@CDs-1.8 / DW are both around 95%. The reason is that the porosity of NW is not as high as that of DW, thereby increasing the energy storage density of the phase change energy storage material. This shows that the phase change energy storage material has an excellent impregnation effect in DW.

[0113] Table 3 Impregnation rate of NW and DW impregnated phase change energy storage materials

[0114]

[0115] The impregnation ratio of PEG in the energy storage material reflects the latent heat efficiency of the phase change energy storage material. The higher the impregnation ratio, the better the latent heat efficiency of the phase change energy storage material. Table 4 shows the encapsulation rate of PEG impregnated in natural wood (NW) and delignified wood (DW). The impregnation rates of PEG / NW and PEG@Fe-CDs-1.8 / NW do not exceed 30%, while the impregnation rate of PEG / DW is 94.70%, because the porosity of NW is not as high as that of DW. The impregnation rate of PEG@Fe-CDs-1.8 / DW is 96.05%. The impregnation rate of the phase change energy storage material loaded with Fe-CDs is slightly higher than that of the phase change energy storage material without Fe-CDs. The reason is that Fe-CDs itself is rich in hydroxyl, amino, and carboxyl functional groups, which can promote the close combination of PEG molecular chains and DW support materials, so it can impregnate more PEG. This shows that polyethylene glycol and iron-doped carbon dots have excellent impregnation effects in DW.

[0116] Table 4 Impregnation rate of NW and DW impregnated phase change energy storage materials

[0117]

[0118] 3.8 Analysis of thermal properties of carbon dots (CDs) and iron-doped carbon dots (Fe-CDs) shaped wood-based phase change energy storage materials

[0119] 3.8.1 Analysis of thermal properties of CDs and Fe-CDs shaped wood-based phase change energy storage materials

[0120] In order to further understand the thermal properties of phase change energy storage materials, PEG@CDs-1.8 / DW phase change energy storage materials were selected for thermal performance research. The thermal performance parameters of phase change energy storage materials were obtained after TG and DSC tests, mainly including phase change temperature and phase change enthalpy. After adding CDs, the melting heat of PEG@CDs / DW decreased with the increase of CDs content ( Fig.12a, Table 5). PEG@CDs-1.8 / DW was selected for the study of the thermal cycling stability of phase change energy storage materials. The melting enthalpy of PEG@CDs-1.8 / DW is 10.1 J / g lower than that of PEG / DW, indicating that CDs occupies part of the volume of the delignified wood pores, so its melting enthalpy decreases slightly, and PEG@CDs-1.8 / DW still exhibits a high melting enthalpy of 139.45 J / g. According to Table 5, the energy storage efficiency of PEG in PEG@CDs-1.8 / DW is 93.25%, which indicates that PEG@CDs-1.8 / DW has excellent heat storage capacity. In order to measure the thermal cycling usability of PEG@CDs-1.8 / DW, 50 heating-cooling cycle tests were carried out, and the results are shown in Table 5. Compared with the phase change temperature and melting enthalpy before the cycle, PEG@CDs-1.8 / DW 50 They show similar phase transition temperatures, and the melting enthalpy is only reduced by 6.2 J / g, which indicates that PEG@CDs-1.8 / DW has a long cycle time and service life. The melting and solidification temperatures of PEG, PEG / DW, and PEG@CDs-1.8 / DW are close, indicating that the polyethylene glycol encapsulation effect is good and its thermal properties are basically unchanged ( Fig.12 a). DW exhibits a one-step thermal degradation starting at about 200°C and ending at 330°C, with the maximum weight loss at 305°C. The thermal degradation of PEG occurs in the range of 310–400°C. CDs have two maximum degradation peaks at 70°C and 340°C, and the degradation at 60°C is due to the mass loss caused by the adsorption of water ( Fig.12 b). The actual degradation temperature of CDs is about 310℃ ( Fig.12 b, c). The thermal degradation temperatures of PEG, PEG / DW, and PEG@CDs-1.8 / DW are close to 400°C, indicating that PEG@CDs-1.8 / DW has good thermal stability and can be used for energy storage applications within 200°C because DW begins to degrade at 200°C. After 50 thermal cycle tests, PEG@CDs-1.8 / DW Fig.12 d), the melting and solidification temperatures did not change significantly and the thermal energy storage efficiency of the phase change energy storage material only decreased by 5.11%, and the phase change energy storage material had good cyclic usability.

[0121] Table 5 Thermal properties of pure polyethylene glycol, wood-based phase change energy storage materials and CDs-loaded wood-based phase change energy storage materials

[0122]

[0123] In order to further understand the thermal properties of phase change energy storage materials, the thermal properties of PEG@Fe-CDs-1.8 / DW phase change energy storage material were studied. The thermal performance parameters of the phase change energy storage material, including phase change temperature and phase change enthalpy, were obtained after TG and DSC tests. The latent heat of PEG@Fe_CDs-1.8 / DW phase change energy storage material is 137.04 J / g, which is 8.99 J / g lower than that of PEG / DW. The reason is that Fe-CDs occupies part of the volume of the delignified wood pores, so its melting enthalpy decreases slightly. The thermal cycling results of PEG@Fe-CDs-1.8 / DW show that compared with the phase change temperature and melting enthalpy before the cycle, after 50 heating-cooling cycle tests, PEG@Fe-CDs-1.8 / DW 50 They showed similar phase transition temperatures (Table 6), and the melting enthalpy was only reduced by 4.6 J / g, which indicated that the PEG@Fe-CDs-1.8 / DW phase change energy storage material had a long cycle life. The melting and solidification temperatures of the three materials, PEG, PEG / DW, and PEG@Fe-CDs-1.8 / DW, were close, indicating that the thermal properties of PEG were basically unchanged, indicating that the polyethylene glycol encapsulation effect was good ( Fig.13 a). Fig.13 (b) DW exhibits a one-step thermal degradation, starting at 200°C and ending at 330°C, with the maximum weight loss rate at 305°C. The thermal degradation of PEG occurs in a one-step degradation in the range of 310-400°C. The thermogravimetric curve of Fe-CDs has two maximum degradation rates at around 70°C and 200°C. The degradation rate at 70°C is due to the mass reduction caused by the adsorption of water by Fe-CDs. The actual degradation temperature of Fe-CDs is about 200°C, because the preparation temperature of Fe-CDs is 180°C, so the thermal degradation temperature will not be lower than 180°C ( Fig.13 c). The thermal degradation temperatures of PEG, PEG / DW, and PEG@Fe-CDs-1.8 / DW are similar at 380°C, indicating that PEG@Fe-CDs-1.8 / DW has good thermal stability and can be used for energy storage applications within 200°C. PEG / DW exhibits two distinct degradation processes at temperatures of 310°C and 370°C, respectively. This is attributed to the degradation of DW and PEG, indicating that the two are not completely tightly combined. However, PEG@Fe-CDs-1.8 / DW only exhibits a one-step degradation process. This is because Fe-CDs contains a large number of hydroxyl and carboxyl functional groups, which are mixed with PEG and impregnated in the delignified pores as "cross-linking points", restricting the movement of PEG molecular chains, and the overall macroscopic performance is that the thermal stability of the phase change energy storage material is improved. After 50 thermal cycle tests on PEG@Fe-CDs-1.8 / DW ( Fig.13 d), the melting and solidification temperatures did not change significantly and the thermal energy storage efficiency of the phase change energy storage material only decreased by 3.59%, which proved that the phase change energy storage material had good thermal cycle performance.

[0124] Table 6 Thermal properties of pure polyethylene glycol, wood-based phase change energy storage materials and Fe-CDs loaded shaped wood-based phase change energy storage materials

[0125]

[0126] 3.8.2 Analysis of photothermal conversion of carbon dots (CDs) and iron-doped carbon dots (Fe-CDs) shaped wood-based phase change energy storage materials

[0127] In order to intuitively understand the heat storage and release process of phase change energy storage materials, an infrared thermal imager was used to record and compare the surface temperature changes of phase change energy storage materials loaded with CDs at different time periods. Fig.14 As shown in the figure, it can be seen that under the xenon lamp (200mW / cm 2 ) Under simulated sunlight, before irradiation (0min), the color of all samples was close to the ambient temperature, and the shape of the samples could not be seen. However, as the irradiation time increased, the shape of the samples gradually became clear and the temperature and color of the sample surface changed. The heating rate and peak temperature of the phase change energy storage material loaded with CDs were higher than those of the phase change energy storage material without CDs, which shows that CDs can indeed improve the photothermal conversion capacity of the phase change energy storage material. By comparing the two energy storage materials PEG / DW and PEG@CDs-1.8 / DW, the heating temperature of the two materials increased from room temperature 26°C to 34.5°C and 54.6°C, respectively, within 35 minutes. Fig.14 ), the photothermal conversion efficiency of PEG@CDs-1.8 / DW phase change material reached 53.16%, and the photothermal conversion efficiency of PEG / DW was 15.53%, indicating that PEG@CDs / DW had good photothermal conversion ability. Its energy storage capacity reached its peak within 35 minutes, and then the xenon lamp was turned off to cool it down at room temperature. It was found that after cooling for 60 minutes, the temperature of the phase change material remained at around 30°C (room temperature was 25°C), indicating that it had good energy storage capacity ( Fig.15 a). Fig.15 As shown in bd, the actual object of the CDs phase change energy storage material and the thermal imaging temperature rise, it rises to 56.2℃ at room temperature 25℃, indicating that it has good application prospects in the field of construction.

[0128] In order to intuitively understand the heat storage and release process of phase change energy storage materials, an infrared thermal imager was used to record the sample temperature. 2) Under simulated sunlight, before irradiation (0min), the color of all samples was close to their ambient temperature, and the shape of the samples could not be seen. However, as the irradiation time increased, the shape of the samples gradually became clearly visible and the temperature and color of the sample surface changed. The heating rate of the phase change energy storage material loaded with Fe-CDs was higher than that of the phase change energy storage material without Fe-CDs. The phase change energy storage material loaded with CDs heated up to 48.7°C within 20min, and the phase change energy storage material loaded with Fe-CDs heated up to 65.4°C within 20min. This shows that Fe-CDs can indeed improve the photothermal conversion capacity of phase change energy storage materials. Under xenon lamp irradiation (200mw / cm 2 ), PEG / DW and PEG@Fe-CDs-1.8 / DW, the temperature increased from room temperature 26℃ to 34.5℃ and 66.4℃ respectively ( Fig.16 ). The photothermal conversion efficiency of PEG@Fe-CDs-1.8 / DW phase change energy storage material reached 71.88%. The photothermal conversion efficiency of PEG / DW phase change material is 15.53%, and the photothermal conversion efficiency of PEG@CDs-1.8 / DW phase change material is 53.16%. Compared with PEG@CDs-1.8 / DW, the photothermal conversion efficiency of the Fe-CDs phase change energy storage material is increased by 35%, indicating that the Fe-CDs phase change energy storage material has better photothermal conversion ability than the CDs phase change energy storage material. In the cooling test, the xenon lamp was turned off to cool it under natural conditions. The Fe-CDs phase change energy storage material cooled relatively slowly. After cooling for 60 minutes, its temperature remained at around 32°C (room temperature was 25°C), indicating that the Fe-CDs phase change energy storage material has the advantages of fast heat absorption and slow heat release ( Fig.17 ). Fig.17 As shown in bd, the actual phase change energy storage material loaded with Fe-CDs and the thermal imaging temperature rise, which rises to 65.3℃ at room temperature 25℃, and its temperature rise is better than the wood-based phase change energy storage material doped with CDs (56.2℃), which has good application prospects in the field of construction.

[0129] 3.8.3 Analysis of the anti-leakage ability of carbon dots (CDs) and iron carbon dots (Fe-CDs) shaped wood-based phase change energy storage materials

[0130] PEG will leak when it is above the phase change temperature, which will reduce the latent heat efficiency of the phase change energy storage material. Therefore, improving the morphological stability of PEG is crucial to promoting the application of phase change materials. The morphological stability photos of three samples were obtained through leakage test: PEG, PEG / DW, and PEG@CDs-1.8 / DW leakage test ( Fig.18 b) by Fig.12(a) Compared with the DSC graph and thermal properties of phase change energy storage materials in Table 5, it can be seen that pure PEG, PEG / DW, and PEG@CDs-1.8 / DW will not undergo phase change at room temperature (25°C), and their phase change temperatures are all around 50°C with intact morphological characteristics. At 60°C, pure PEG has undergone an obvious phase change, and a large amount of PEG has changed into liquid. A small amount of PEG leakage occurs in PEG / DW, while no obvious leakage occurs in the carbon dot-doped PEG@CDs-1.8 / DW phase change energy storage material. A small amount of PEG leakage occurs in PEG / DW because wood itself contains abundant hydroxyl functional groups, which easily combine with the hydroxyl groups of polyethylene glycol to form hydrogen bonds, which has a certain inhibitory effect on the leakage of PEG during the phase change process. The PEG@CDs-1.8 / DW phase change energy storage material did not leak significantly. On the one hand, this was due to the hydrogen bonding and capillary action between PEG and the wood pores. On the other hand, CDs contained a large number of hydroxyl and carboxyl functional groups, which were mixed with PEG and impregnated in the delignified pores to serve as "cross-linking points" to limit the movement of PEG molecular chains. Overall, the anti-leakage ability of the phase change energy storage material was improved ( Fig.18 a).

[0131] The results of the leak test show that ( Fig.19 ), PEG / DW and PEG@Fe-CDs-1.8 / DW showed good anti-leakage ability at room temperature (25℃). When the temperature rose to 60℃, pure PEG had obvious leakage, and PEG / DW also had a small amount of PEG leakage. In contrast, PEG@Fe-CDs-1.8 / DW phase change energy storage material did not leak. This is mainly attributed to the fact that the shaping ability of the phase change energy storage material loaded with Fe-CDs is similar to that of the phase change energy storage material loaded with CDs. The reason for this is that on the one hand, the rich hydroxyl functional groups contained in the wood itself can form hydrogen bonds with the hydroxyl groups of polyethylene glycol, which has a certain inhibitory effect on the leakage of the phase change process of PEG. On the other hand, Fe-CDs plays a key role. It contains a large number of hydroxyl, carboxyl, and amino functional groups, which can form a "cross-linking effect" with PEG and DW, further limiting the leakage of PEG molecular chains in the wood pores. Therefore, this dual effect jointly improves the anti-leakage ability of the phase change energy storage material.

[0132] <Example>

[0133] A light-responsive Fe 3+ Preparation method of carbon doped wood-based phase change energy storage material, a light-responsive Fe 3+ A method for preparing a carbon dot-doped wood-based phase change energy storage material comprises the following steps:

[0134] Step 1: Fe 3+ 9 mg of doped carbon dot powder was dissolved in 5 mL of anhydrous ethanol to obtain Fe3+ doping carbon dot solution;

[0135] Among them, Fe 3+ The preparation method of the doped carbon dot powder is as follows: 0.1 g of dopamine hydrochloride, 0.1 g of o-phenylenediamine, 0.05 g of ferric chloride hexahydrate and 15 mL of anhydrous ethanol are stirred and dissolved, and then placed in a tetrafluoroethylene-lined reactor; the reactor is then transferred to a muffle furnace for heating reaction at a temperature of 180°C for a reaction time of 12 hours; after the heating is completed, the solution in the reactor is centrifuged at a speed of 8000 r / min for 15 minutes, and the supernatant is placed in a dialysis bag for dialysis (molecular weight = 1000 Da) for 48 hours; after the dialysis is completed, the dialysate is subjected to vacuum freeze drying for 48 hours to obtain Fe 3+ Doped carbon dot solid powder;

[0136] Step 2: Weigh 30 g of polyethylene glycol (molecular weight 2000 g / mol) and melt it in a water bath at 70°C. Pour Fe 3+ The doped carbon dots solution was stirred in a water bath for 20 min to mix evenly, and Fe-CDs@PEG composite phase change material was obtained;

[0137] Step 3: The Fe-CDs@PEG composite phase change material is placed in a 70°C constant temperature vacuum box to make it molten, and then the delignified wood is added to evacuate the vacuum, and the pressure is restored to normal. The vacuum-assisted impregnation process of evacuating the vacuum and restoring the pressure is repeated 3 times. The sample is taken out and the surface phase change material is wiped off with filter paper to obtain Fe 3+ Carbon doped wood-based composite phase change energy storage materials;

[0138] Among them, the preparation method of delignified wood is to prepare a sodium chlorite solution with a mass fraction of 1%, adjust the pH value to 4.6 with glacial acetic acid, add balsa wood chips with a size of 30×30×3mm to the solution, place it in an environment of 80°C for 18 hours until the color turns white to remove lignin, end the water bath, and then use deionized water to wash the delignified wood sample three times, and perform ultrasonic cleaning in deionized water for 20 minutes to remove most of the chemical residues. After completing the ultrasonic cleaning, the delignified wood is placed in a refrigerator for freezing for 12 hours, and then vacuum freeze-dried for 24 hours to obtain delignified wood.

[0139] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. Light-responsive Fe 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The following steps are involved: Step 1: Fe 3+ The doped carbon dot powder was dissolved in ethanol to obtain Fe 3+ doping carbon dot solution; Step 2: Melt polyethylene glycol in a water bath and pour in Fe 3+ The doped carbon dots solution was stirred and mixed to obtain Fe-CDs@PEG composite phase change material; Step 3: The Fe-CDs@PEG composite phase change material is placed in a constant temperature vacuum box to make it in a molten state, and then the delignified wood is added and vacuumed to restore the normal pressure. The sample is taken out and the surface phase change material is wiped off with filter paper to obtain Fe 3+ Carbon dot-doped wood-based composite phase change energy storage materials.

2. The photoresponsive Fe according to claim 1 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: Fe 3+ The preparation method of the doped carbon dot powder is to take dopamine hydrochloride, o-phenylenediamine, ferric chloride hexahydrate and anhydrous ethanol, stir and dissolve them, and then place them in a tetrafluoroethylene lined reactor; Then the reactor is transferred to a muffle furnace for heating reaction; after the heating is completed, the solution in the reactor is centrifuged, and the supernatant is placed in a dialysis bag for dialysis; after the dialysis is completed, the dialysate is subjected to vacuum freeze-drying treatment to obtain Fe 3+ Doped carbon dot solid powder.

3. The photoresponsive Fe according to claim 2 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The mass ratio of dopamine hydrochloride, o-phenylenediamine and ferric chloride hexahydrate is 1-5:1-5:

1.

4. The photoresponsive Fe according to claim 2 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The temperature of the Ma boiling furnace is 180-220℃ and the reaction time is 10-12h.

5. The photoresponsive Fe according to claim 2 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The centrifugal speed was 8000 r / min and the centrifugal time was 15 min.

6. The photoresponsive Fe according to claim 2 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The molecular weight of the dialysis bag is 1000Da and the dialysis time is 40-50h.

7. The photoresponsive Fe according to claim 2 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The drying time is 14-48h.

8. The photoresponsive Fe according to claim 1 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The mass ratio of polyethylene glycol to Fe3+ doped carbon dot powder is 3000-4000:

1.

9. The photoresponsive Fe according to claim 1 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: The preparation method of delignified wood comprises the following steps: preparing a sodium chlorite solution with a mass fraction of 0.1-2%, adjusting the pH value to 4-5, adding wood chips to the solution, performing water bath treatment to remove lignin, and performing vacuum freeze drying treatment after the water bath is finished to obtain delignified wood.

10. The photoresponsive Fe according to claim 1 3+ The method for preparing a carbon dot-doped wood-based phase change energy storage material is characterized in that: In step 3, the operation of evacuating the air and restoring the pressure to normal is repeated 1 to 5 times.